2021
DOI: 10.1186/s40658-021-00353-y
|View full text |Cite
|
Sign up to set email alerts
|

A methodological investigation of healthy tissue, hepatocellular carcinoma, and other lesions with dynamic 68Ga-FAPI-04 PET/CT imaging

Abstract: Background The study aimed to establish a 68Ga-FAPI-04 kinetic model in hepatic lesions, to determine the potential role of kinetic parameters in the differentiation of hepatocellular carcinoma (HCC) from non-HCC lesions. Material and methods Time activity curves (TACs) were extracted from seven HCC lesions and five non-HCC lesions obtained from 68Ga-FAPI-04 dynamic positron emission tomography (PET) scans of eight patients. Three kinetic models we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
(9 reference statements)
1
16
0
Order By: Relevance
“…A previously conducted study supports these ndings, as it indicates that FAPI scans of patients with hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCC) seem to be equivalent to contrast enhanced computed tomography (CE-CT) and magnetic resonance imaging (MRI) and even superior to FDG-PET/CT (14). Moreover, FAPI-PET/CT imaging of liver lesions was capable of successfully distinguishing between HCC, non-HCC and normal liver parenchyma (15). CCC (n=5) in particular presented an exceedingly high mean uptake with a SUVmax of 11 (range 3.9-26).…”
Section: Discussionmentioning
confidence: 67%
“…A previously conducted study supports these ndings, as it indicates that FAPI scans of patients with hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCC) seem to be equivalent to contrast enhanced computed tomography (CE-CT) and magnetic resonance imaging (MRI) and even superior to FDG-PET/CT (14). Moreover, FAPI-PET/CT imaging of liver lesions was capable of successfully distinguishing between HCC, non-HCC and normal liver parenchyma (15). CCC (n=5) in particular presented an exceedingly high mean uptake with a SUVmax of 11 (range 3.9-26).…”
Section: Discussionmentioning
confidence: 67%
“…They also reported two patients with benign nodules that were 68 Ga-FAPI negative and highlighted its potential in differentiating benign from malignant lesions. Similarly, the ability of dynamic 68 Ga-FAPI04 PET/CT in differentiating HCC from non-HCC lesions has also been demonstrated in a brief report (51). 68 Ga-FAPI04 PET/CT was compared with contrast-enhanced CT in 19 pancreatic ductal adenocarcinoma patients, and 68 Ga-FAPI04 PET/CT results changed TNM staging in 10 patients.…”
Section: Fibroblast Activation Protein-targeted Imaging In Oncologymentioning
confidence: 76%
“…Guo et al (50) Liver malignancies 34 The sensitivity of 68 Ga-FAPI04 PET/CT in detecting primary and metastatic liver lesions is equivalent to that of contrast-enhanced CT and MRI and better than 18 F-FDG PET/CT. Geist et al (51) Hepatic lesions 8 Dynamic 68 Ga-FAPI PET scan allows differentiation between hepatocellular carcinoma and non-HCC lesions Röhrich et al (52) Pancreatic ductal adenocarcinomas 19 68 Ga-FAPI PET/CT allowed restaging in half of the patients with PDAC and the majority of patients with recurrent disease compared with standard-of-care imaging. Liermann et al (53) Pancreatic cancer 7 FAPI PET/CT seems to be a superior imaging modality to contrast-enhanced CT, which is the current gold standard in pancreatic cancer with the potential as a tool for automatic target volume definition before radiotherapy.…”
Section: Syed Et Al (36)mentioning
confidence: 99%
“…In 12/23 studies [ 68 Ga]Ga-FAPI was offered as a compassionate drug according to the German Medicinal Product Act § 13(2b) [25,26,35,36,[27][28][29][30][31][32][33][34]. In the remaining 10/23 papers, the trial phase was not speci ed or designated as "not applicable" [37][38][39][40][41][42][43][44][45][46]. In 18/23 studies [ 68 Ga]Ga-FAPI imaging was compared to other imaging technique(s).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…On the other hand, the automatically contoured [ 68 Ga]Ga-FAPI-GTV was similar in size to four out of six manually drawn ceCT-GTV, and when reviewing cases, the [ 68 Ga]Ga-FAPI-GTV matched convincingly well the GTV drawn by the six radiation oncologists.3.2.2.3 Oncological studies focused on biodistribution and kineticsRöhrich et al 2020[27] found a moderately positive correlation between FAP-speci c signals and relative cerebral blood volume values, but not with the apparent diffusion coe cient in MRI, suggesting the independence of [ 68 Ga]Ga-FAPI uptake from perfusion and cell density. Geist et al[40] evaluated through different models the time-activity curves extracted from eight dynamic [ 68 Ga]Ga-FAPI-04 PET/CT to assess the discriminant capability of kinetic parameters in differentiating healthy tissue, HCC, and non-HCC lesions. The ndings of this preliminary study suggested a two-compartmental model assess [ 68 Ga]Ga-FAPI kinetics.…”
mentioning
confidence: 99%